Green HRM and prosocial rule-breaking: role of climate, intentions, and CSR - Yan, Li; John, Albert; Saleem, Sidra; Mohelska, Hana; Jiang , Mingdi (Transformations In Business & Economics, 2025)
Drawing on the social exchange theory, this research examines how green HRM encourages prosocial rule-breaking through a green psychological climate and behavioural intentions. A time-lagged survey design was used to collect data from 230 employees across various organisations in Pakistan. Structural equation modelling is used to test the direct and indirect effects of green HRM on prosocial rule-breaking. Results show that green HRM does not directly influence prosocial rule-breaking. Its impact is mediated through green psychological climate and behavioural intentions. Moreover, external CSR negatively affects the relationship between green HRM and the green psychological climate. This challenges the common belief that CSR always plays a supportive role. These findings offer valuable insights for researchers and organisations looking to enhance sustainability-driven innovation and encourage discretionary behaviours. The study provides implications for both researchers and practitioners. Future research direction is offered to strengthen the field of sustainability and green HRM.
Keywords: human resource management; corporate social responsibility; prosocial rule-breaking; green psychological climate; green behavioural intentions